The Effect of Information and Threat Emotion on Buying Decision of Masks by the Indonesian Community in Preventing Covid-19 Virus - Wilda Nasution; Ratih Hasanah Sudrajat (Jurnal Spektrum Komunikasi, 2022)
In making buying decisions, consumers are always driven by needs or motivation. Many previous studies have proven the role of various forms of motivation in influencing the judgment that leads to buying decisions. One form of motivation is the threat emotion. Not much research has been done on how emotions influence consumer decision making. Fear turns out to be an internal pressure for consumers and urges them to reduce tension by making decisions. Using data obtained from 400 respondents, this study aims to measure the influence of information and threat emotion on the decision to buy masks by the Indonesian people to prevent the Covid-19 virus. The results show the significant influence of information and threat emotion on their purchase decisions because they believe that masks are the answer to prevent and reduce their fear of the Covid-19 virus.